The Fate of Normocalcemic Hyperparathyroidism: Insights from a 3-Year Multicenter Follow-Up - Tuna, Mazhar Muslum; Aycicek, Bercem; Engin, Ismail; Canpolat, Asena Gokcay; Kir, Yusuf; Tufan, Ceren; Sari, Ramazan (Georg Thieme Verlag Kg, 2026)
Normocalcemic primary hyperparathyroidism is thought to be an early form of hypercalcemic primary hyperparathyroidism. However, some studies have shown progression to hypercalcemia, hypercalciuria or kidney stones, bone loss and fractures in a proportion of patients over time, whereas other studies have not observed such outcomes. The aim of this study was to investigate the clinicopathological features and natural history of the disease in a large patient population and to provide clinicians with strong evidence-based recommendations. This is a nationwide, multicenter, observational, retrospective cohort study. Tertiary healthcare endocrinology departments were the setting for this study. Data from different regions of Turkey, including 527 patients, were included in this study. A total of 123 patients were not eligible for inclusion, and the remaining 404 patients were included in the final analysis. All laboratory assessments, dual-energy X-ray absorptiometry and renal ultrasound were performed locally at each center at baseline and several times during follow-up. The mean age was 54.63 +/- 11.41 years. As expected, there was a female predominance of 362 (89.4%). A total of 376 patients were followed up for 1 year and 252 patients for 3 years. Forty-seven out of 404 patients (11.6%) developed hypercalcemia within 3 years. Twenty-eight patients became hypercalcemic within the 1 st year, and 19 patients became hypercalcemic within 3 years. Among the 47 patients, only four patients had a calcium level above 11 mg/dL during the follow-up. Nephrolithiasis was detected in 50 patients (12.6%). There was no significant difference in calcium, parathyroid hormone, 25-hydroxyvitamin D, or urinary calcium levels or the presence of nephrolithiasis. Bone mineral density assessments revealed that only 90 patients (28.5%) had normal bone mineral density. A total of 135 (42.7%) patients had osteopenia, and 91 (28.8%) patients had osteoporosis at least one site at presentation. This study revealed that patients with normocalcemic primary hyperparathyroidism have significant adverse skeletal outcomes, a slight increase in kidney stones. Only a small proportion of patients develop hypercalcemia, and the risk of developing significant hypercalcemia that would alter the patient's treatment management is much lower.
Keywords: normocalcemic primary hyperparathyroidism; primary hyperparathyroidism; bone/calcium homeostasis; hyperparathyroidism; hypercalcemia